In it Together? An Exploration of the Moral Duties of Co‐parents. Issue 5 (27th April 2021) - Cutas, Daniela; Hohl, Sabine
Abstract: Even though co‐parenthood is one of the most significant close personal relationships that people can have, there is relatively little philosophical work on the moral duties that co‐parents owe each other. This may be due to the increasingly questionable assumption, still common in our societies, that co‐parenthood arises naturally from marriage or romantic coupledom and thus that commitment to a co‐parent evolves from a commitment to a marital or romantic partner. In this article, we argue that co‐parenthood should be seen as a relationship in its own right, which generates specific moral duties. Co‐parents should come to explicit agreements with each other regarding the most important areas of potential conflict between them. Such agreements may have to be renegotiated over time. We explore some possible non‐negotiable co‐parental duties such as the duties not to alienate the child from the other parent(s) and not to trap a co‐parent in a particularly vulnerable situation. We consider some legal and societal implications of our argument and, finally, suggest some pragmatic benefits of our proposal.